2018
DOI: 10.1016/j.molcel.2018.08.014
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA CamK-A Regulates Ca2+-Signaling-Mediated Tumor Microenvironment Remodeling

Abstract: Cancer cells entail metabolic adaptation and microenvironmental remodeling to survive and progress. Both calcium (Ca) flux and Ca-dependent signaling play a crucial role in this process, although the underlying mechanism has yet to be elucidated. Through RNA screening, we identified one long noncoding RNA (lncRNA) named CamK-A (lncRNA for calcium-dependent kinase activation) in tumorigenesis. CamK-A is highly expressed in multiple human cancers and involved in cancer microenvironment remodeling via activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(87 citation statements)
references
References 25 publications
2
82
0
3
Order By: Relevance
“…The understudied multi-functional CAMK kinases ( CAMK1D, CAMK1G, CAMKK1, PNCK ) are overexpressed in 12 cancers, with PNCK being overexpressed in 9 alone. PNCK (Tbio) mRNA expression and activity has recently been linked to renal cell carcinoma progression and survival [10], breast cancer tumor microenvironment remodeling [31] and decreased sensitivity to chemotherapies such as temozolomide [32]. PNCK is highly overexpressed in KIRC (>5 log 2 FC), LUSC (>6 log 2 FC), and LIHC (>6 log 2 FC).…”
Section: Resultsmentioning
confidence: 99%
“…The understudied multi-functional CAMK kinases ( CAMK1D, CAMK1G, CAMKK1, PNCK ) are overexpressed in 12 cancers, with PNCK being overexpressed in 9 alone. PNCK (Tbio) mRNA expression and activity has recently been linked to renal cell carcinoma progression and survival [10], breast cancer tumor microenvironment remodeling [31] and decreased sensitivity to chemotherapies such as temozolomide [32]. PNCK is highly overexpressed in KIRC (>5 log 2 FC), LUSC (>6 log 2 FC), and LIHC (>6 log 2 FC).…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence has shown that dysregulated lncRNAs, as RNA molecules, contribute to various cancer hallmarks. [ 11 ] We found that lncRNA LOC90024 actually encodes a 130‐aa small protein, which we named SRSP. LOC90024 ‐encoded small protein SRSP, but not LOC90024 lncRNA itself, exerts oncogenic functions.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, dysregulation of lncRNAs in cancers contributes to the hallmarks of cancers and the survival time of cancer patients; thus, they are attractive potential biomarkers and therapeutic targets. [ 8,10,11 ] However, the functional roles of lncRNA in “cancerous” RNA splicing remain to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of tumour cells to regulate the local nutrients 91 and waste products of tumour metabolism also play a critical role in determining the fate of metabolic deregulation of cancer. 92 Moreover, recent emergence of LncRNAs and their metabolic implication in cancers [93][94][95] provides an interesting dimension to this multi-headed disease.…”
Section: Immunometabolism In Metabolic Dere Gulationmentioning
confidence: 99%